Acute lethal effect of the commercial formulation of the insecticides Imidacloprid, Spinosad y Thiocyclam hidrogenoxalate in Bombus atratus (Hymenoptera: Apidae) workers - Riaño Jiménez, Diego (2016)
The effect of insecticides on bees has gained great attention, however, there are few studies that explore this issue on Neotropical bees. Bombus atratus is a neotropical species broadly distributed in Colombia and is considered an important pollinator of both Andean ecosystems and agroecosystems. However, as for many wild bees species, the effect of insecticides on B. atratus is unknow. In this study we determined the acute median lethal dose (LD50) of commercial formulations of insecticides Imidacloprid, Spinosad and Thiocyclam hydrogen oxalate, widely used in Colombia to control several pests of important crops. The LD50 was carried out by oral and contact routes, following and modifying the EPPO and OECD guidelines to perform LD50 on A. mellifera. We evaluated five doses for each route and insecticide, in a total of 25 medium-size workers for each dose by duplicate. Mortality was registered at 24, 48 and 72 hours after the experiment; and data were analyzed with the Probit regression model. For Imidacloprid, contacts and oral LD50 were 0.048 µg/bee and 0.010 µg/bee, respectively. For Thiocyclam hydrogen oxalate, topical and oral LD50 were 0.244 µg/bee and 0.056 µg/bee, respectively. For Spinosad, the oral LD50 corresponded to 0.28 µg/bee; it was not possible to establish the LD50 for the contact route. The Hazard Quotient (HQ) and Index of Relative Toxicity indicated that all three active ingredients are highly toxic. We discussed the risk of the insecticides use on B. atratus, considering their chemical nature.